Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.chom.2015.08.009
|View full text |Cite
|
Sign up to set email alerts
|

BIRC2/cIAP1 Is a Negative Regulator of HIV-1 Transcription and Can Be Targeted by Smac Mimetics to Promote Reversal of Viral Latency

Abstract: SUMMARY Combination antiretroviral therapy (ART) is able to suppress HIV-1 replication to undetectable levels. However, the persistence of latent viral reservoirs allows for a rebound of viral load upon cessation of therapy. Thus, therapeutic strategies to eradicate the viral latent reservoir are critically needed. Employing a targeted RNAi screen, we identified the ubiquitin ligase BIRC2 (cIAP1), a repressor of the noncanonical NF-κB pathway, as a potent negative regulator of LTR-dependent HIV-1 transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
152
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(167 citation statements)
references
References 35 publications
9
152
0
Order By: Relevance
“…Most Smac proteins directly compete with caspases for XIAP binding, liberating caspases for apoptosis. Smac proteins can also activate the ubiquitin activity of cIAP1/2 leading to the degradation of these IAPs (Pache et al, 2015). Through their ability to bind and inhibit IAP activity, Smac mimetics can induce pro-apoptotic mechanisms and therefore are attractive compounds to induce the apoptosis of reactivated, latently infected cells.…”
Section: Pro-apoptotic Compounds To Clear Hiv Latently Infected T-cellsmentioning
confidence: 99%
“…Most Smac proteins directly compete with caspases for XIAP binding, liberating caspases for apoptosis. Smac proteins can also activate the ubiquitin activity of cIAP1/2 leading to the degradation of these IAPs (Pache et al, 2015). Through their ability to bind and inhibit IAP activity, Smac mimetics can induce pro-apoptotic mechanisms and therefore are attractive compounds to induce the apoptosis of reactivated, latently infected cells.…”
Section: Pro-apoptotic Compounds To Clear Hiv Latently Infected T-cellsmentioning
confidence: 99%
“…Inhibition of cIAP1 by SMAC mimetics leads to the accumulation of NIK, phosphorylation of IKKα, and the subsequent processing of p100 to p52. RelB/p52 heterodimers then translocate to the nucleus where they induce NF-κB-dependent transcription, including triggering transcription of latent proviruses (81). In vitro studies of HDAC inhibitor/SMAC/XIAP mimetic combinations demonstrated potent synergistic activities between these two classes of compounds(81).…”
Section: Smac Mimetics and The Non-canonical Nf-κb Activation Pathwaymentioning
confidence: 99%
“…Recently, IAP1/2 and survivin, another member of the IAP family were suggested to be involved in survival of HIV-infected CD4+ T cells [46,47]. In addition, IAPs have been implicated in protection against hepatitis B infection and in the reversal of HIV latency in CD4+ T cells [48,49]. Using HIV-Vpr as an apoptosis-inducing agent, we have shown a protective role for IAP genes in resistance to cell death in Mφ [50][51][52].…”
Section: Introductionmentioning
confidence: 86%
“…Apoptosis has been shown to induce viral activation and replication in latently infected U1 and ACH2 cell lines [56]. In addition, Pache et al have shown that SMs can affect viral transcription in infected CD4 + T cells via NF-κB dependent signalling [49]. To determine if SMs affect HIV replication in Mϕ, in vitro HIV-infected MDM were treated with SM -LCL161 for 48 hr followed by analysis of p24 secretion.…”
Section: Sms Induce Cell Death In In Vitro Hiv-infected Mdms and Mdmsmentioning
confidence: 99%